Desarrollo de un sistema web para agilizar procesos administrativos de gestión documental en el Registro de la Propiedad del Gobierno Autónomo Descentralizado de Chone - Avellán Vera, Diego Alexander (2025)
The main objective of the project was to develop a web system for the administrative processes of document management at the Property Registry in Chone Municipal GAD. The methodology was applied in three phases: in the first phase, the system requirements were identified using research techniques and the IEEE 830 standard. Subsequently, the agile SCRUM methodology was adopted, organizing the work into sprints with a particular focus on user stories. Finally, the database, use case diagrams, and navigation diagrams were designed. Additionally, the backend was developed using Laravel 10 and Livewire 3. The frontend was built using Bootstrap and JavaScript, and Visual Studio Code was used as the IDE in a development environment with XAMPP. The result was a local web system that allowed users to perform procedures for registrations, certifications, return notes, and integration between departments. Moreover, the system facilitated the subsequent search and retrieval of information through detailed reports. The system significantly improved document management, achieving the proposed objectives and resulting in greater efficiency and user satisfaction.